Cover Image. (14th March 2022) - Gifford, Linda; Johnson, Christine C.; Haque, Nadia; Passalacqua, Karla D.; Swiderek, Jennifer; Kalkanis, Steven
Abstract : The cover image is based on the Perspective Article COVID‐19 in the hotspot of Metropolitan Detroit: A multi‐faceted health system experience by Linda Gifford et al. https://doi.org/10.1002/hpm.3392 .